ГИГИЕНИЧЕСКАЯ ОЦЕНКА КРИТЕРИЕВ БЕЗОПАСНОСТИ И ПИЩЕВОЙ ЦЕННОСТИ ПЛОДООВОЩНОЙ ПРОДУКЦИИ (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
Soil and climatic conditions, timeliness and quality of agrotechnical measures and the application of mineral fertilizers are undoubtedly the leading factors determining the yield of agricultural crops. The growing use of fertilizers is scientifically regulated by appropriate calculations based on the dynamic levels of soil nutrients during intensive crop production. At the same time, as agriculture intensifies, profound changes are occurring in the plant-soil relationship.